```Question 409321
You are pretty close. Other than not finishing, the only mistake is that your "+-" is in the wrong place. It belongs in front of the square root. The Quadratic Formula is:
{{{x = (-b +- sqrt(b^2-4ac))/2a}}}<br>
With the "+-" in the right place, you are totally correct up to:
{{{x = (-17 +- sqrt((9)(121)))/40}}}
Next we use a property of radicals, {{{root(a, p*q) = root(a, p)*root(a, q)}}}, to split the square root of the product into the product of the square roots of the factors:
{{{x = (-17 +- sqrt(9)*sqrt(121))/40}}}
Now, just like you had, {{{sqrt(9) = 3}}}. What you didn't realize is that 121 is also a perfect square! {{{11^2 = 121}}} so {{{sqrt(121) = 11}}}. Replacing these square roots with these whole numbers we get:
{{{x = (-17 +- 3*11)/40}}}
which simplifies to:
{{{x = (-17 +- 33)/40}}}
This is as far was we can go with the "+-". Next we write this "the long way":
{{{x = (-17 + 33)/40}}} or {{{x = (-17 - 33)/40}}}
Simplifying each we get:
{{{x = 16/40}}} or {{{x = (-40)/40}}}
{{{x = 2/5}}} or {{{x = -1}}}```